1998
DOI: 10.1111/j.1547-5069.1998.tb01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Research in Finland from 1958 to 1995

Abstract: In the future, research is recommended in nursing care of children and adolescents as well as evaluative research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Endeavours to increase research awareness and to train students have been extensive. Similar research training schedules have been reported across Britain and elsewhere (Castles 1984, Ackerman 1997, Bakker & Finch 1998, Leino‐Kilpi & Suominen 1998), and are in line with efforts to help students increase their skills in evaluating, conducting, and writing‐up research (Fosbinder & Loveridge 1996, Bartholomew & Davies 1997, Clifford 1997, Fennessy 1997, Clarke‐Steffen & Stewart 1998). In addition, nursing journals have published self‐help articles on research methodology (Beck 1997, Cowman 1997).…”
Section: Introductionsupporting
confidence: 69%
“…Endeavours to increase research awareness and to train students have been extensive. Similar research training schedules have been reported across Britain and elsewhere (Castles 1984, Ackerman 1997, Bakker & Finch 1998, Leino‐Kilpi & Suominen 1998), and are in line with efforts to help students increase their skills in evaluating, conducting, and writing‐up research (Fosbinder & Loveridge 1996, Bartholomew & Davies 1997, Clifford 1997, Fennessy 1997, Clarke‐Steffen & Stewart 1998). In addition, nursing journals have published self‐help articles on research methodology (Beck 1997, Cowman 1997).…”
Section: Introductionsupporting
confidence: 69%
“…Some studies have been bibliometric analyses involving quantification of information from electronic databases over a specified period e.g., Rafferty, Traynor, and Lewison (2000) and Traynor, Rafferty, and Lewison (2001) in the UK; Huang, Ho, and Chuang (2006) in Taiwan; and Pardo, Reolid, Delicado, Mallebrera, and Garcia‐Messeguer (2001) in Spain. A major alternative has involved analyses of information extracted from journal articles or abstracts e.g., Borbasi, Hawes, Wilkes, Stewart, and May (2002) in Australia; McCarthy, Hegarty, and O'Sullivan (2006) in Ireland; Bongiorno, Colleoni, and Casati (2005) in Italy; Leino‐Kilpi and Suominen (1998) in Finland; and Lin and Lu (2007) in Taiwan.…”
mentioning
confidence: 99%
“…Finally, in the analysis for trend, only quantitative data were considered, excluding the influences that may have been determined by the evolution of nursing education, research, and other factors as recommended by Leino-Kilpi and Suominen (1988). Future studies in this field should also analyze the social and historical influences and include the broader context to explain emerging trends.…”
Section: Limitationsmentioning
confidence: 99%